An Experimental Investigation on Mechanical and Durability Properties of High Strength Fiber Reinforced Concrete (International Journal of Scientific Research and Management (IJSRM), 2015)
At present a large scale production of cement is useful for construction which causes global warming on one side and depletion of natural resources on other side. So that different pozzolanic materials like silica fume, Fly ash, are used in concrete as admixtures. The present study was to evaluate the mechanical and durability properties of M60 grade concrete by replacing 10%, 15% of silica fume and 10%, 20%, 30% of fly ash to cement. 0.5% steel hook fibers are used by volume fraction as admixture for all proportions of HSFRC. The main objective of the present work is to develop M60 grade concrete and to find the effective dosage of silica fume and fly ash. This paper presents the detailed experimental study on compressive strength at different ages i.e. 3 days, 7 days, 28 days, 56 days, 90 days and split tensile test and flexural strength at the age of 28 days. Durability tests like Rapid Chloride Permeability test and Water Absorption test were conducted on casted specimens.